"Casita-Hogar in my Kindergarten" program to develop autonomy in children of 5 years of the initial level Simbal district (Revista Electrónica Diálogos Educativos. REDE, 2017)
The aim of this investigation was to determine the effect of the implementation of the program: "Casita - home in my kindergarten" in the development of autonomy in children of five years at the initial level; using a quasi-experimental design of two groups, made up of fourteen children each, in the Simbal district of the province of Trujillo, Perú, 2016.The data was obtained by applying an observation guide, based on a test evaluation practice of autonomy.The results showed that all children (100%), to which the said program was implemented, improved their autonomy and its dimensions: identity and self-regulation of emotions at the highest level of the scale considered. Likewise, when assessing the difference between the average development of autonomy and its two dimensions considered in the research among children whom the program was applied and not applied to, with the statistical Student t test with α = 0.05 level of significance; it was established that this difference is highly significant because the p value in each case is 0,000.